Genetic Variability of Morphological, Flowering, and Biomass Quality Traits in Hemp (Cannabis sativa L.) - Petit, Jordi; Salentijn, Elma M. J.; Paulo, Maria-João; Thouminot, Claire; van Dinter, Bert Jan; Magagnini, Gianmaria; Gusovius, Hans-Jörg; Tang, Kailei; Amaducci, Stefano; Wang, Shaoliang; Uhrlaub, Birgit; Müssig, Jörg; et al. (Frontiers in Plant Science, 2020)
Hemp (Cannabis sativa L.) is a bast-fibre crop well-known for the great potential to produce sustainable fibres. Nevertheless, hemp fibre quality is a complex trait and little is known about the phenotypic variability and heritability of fibre quality traits in hemp. The aim of this study is to gain insights into the variability in fibre quality within the hemp germplasm and to estimate the genetic components, environmental components and genotype-by-environment (G×E) interactions on fibre quality traits in hemp. To investigate these parameters, a panel of 123 hemp accessions was phenotyped for 28 traits relevant to fibre quality at three locations in Europe, corresponding to climates of northern, central and southern Europe. In general, hemp cultivated in northern latitudes showed a larger plant vigour while earlier flowering was characteristic of plants cultivated in southern latitudes. Extensive variability between accessions was observed for all traits. Most cell wall components (contents of monosaccharides composing cellulose and hemicellulose; and lignin content), bast fibre content and flowering traits revealed large genetic components with low G×E interactions and high broad-sense heritability values, making these traits suitable to maximise the genetic gains of fibre quality. In contrast, contents of pectin-related monosaccharides, most agronomic traits and several fibre traits (fineness and decortication efficiency) showed low genetic components with large G×E interactions affecting the rankings across locations. . These results suggest that pectin, agronomic traits and fibre traits are unsuitable targets in breeding programs of hemp, as their large G×E interactions might lead to unexpected phenotypes in untested locations. Furthermore, all environmental effects on the 28 traits were statistically significant, suggesting a strong adaptive behaviour of fibre quality in hemp to specific environments. The high variability in fibre quality observed in the hemp panel, the broad range in heritability and adaptability among all traits prescribe positive prospects for the development of new hemp cultivars of excellent fibre quality.